Learner Advocates: Co-Designing Disability Awareness and Civic Engagement in Inclusive Higher Education - Aston, Desmond; Rath, Vivian (AHEAD, 2026)
Across Irish higher education, inclusive programmes for people with intellectual disabilities continue to expand. However, opportunities for learners to actively shape teaching, learning, and institutional culture remain limited. Disability awareness initiatives are often well intentioned, yet they frequently speak about disabled people rather than being led by them. The Learner Advocates project emerged from a desire to explore what becomes possible when students with intellectual disabilities are positioned as designers and leaders of disability awareness work within a university setting. This article shares reflections from the Learner Advocates project, developed within an inclusive higher education programme in Ireland. It does not present research findings or theory but instead offers insights from practice, focusing on co-design, learner leadership, and civic engagement, and considers what these approaches can contribute to inclusive practice across further and higher education.
PUBLISHED
Keywords: Inclusive Society; Disability Inclusion; Higher Education; INTELLECTUAL DISABILITY; Inclusive Education; Special Education; Special Needs Education; Intellectual Disability; Education